Experimental and computational comparison of a low heat rejection engine with a conventionally cooled engine - Beard, Joseph G., author; Sampath, Walajabad S., advisor; Beebe, Joseph, committee member; Klarstrom, Dwaine, committee member; Willson, Bryan D., committee member (Colorado State University. Libraries, 2006)
The objective of this dissertation is to determine if, in practice, there are performance gains to be realized from insulating the combustion chamber of a diesel engine and, if so, what degree of insulation is desirable. The effect of partially insulating the combustion chamber of a single cylinder diesel engine is examined. The experimental data collected from running an uninsulated and partially-insulated test engine at various speeds and loads are used to calibrate computer simulations of the test engine. The computer simulation programs, namely Kiva Lite, Wave, and JLAnalyzer, collectively comprise the computational model which was then altered to extend analyses to modifications not attempted experimentally. From the computational model, the optimal exhaust turbine and intake compressor combination for several cylinder insulation levels was determined. The models revealed that there is some performance enhancement to be gained by optimizing engine insulation levels, but that intra-cycle heat transfer limits the efficiency gains to 1% for the Lister-Petter test engine that was modeled. An exact solution to the simplified cylinder heat transfer problem is coupled to an idealized diesel cycle and used to examine the heat transfer mechanisms that limit the efficiency gains as engine insulation is increased.
Keywords: mechanical engineering